MEMBENTUK KARAKTER MELALUI PENDIDIKAN MORAL PADA ANAK USIA DINI DI SEKOLAH RAUDHATUL ATHFAL (R.A) HABIBILLAH - Gunadi, R. Andi Ahmad (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
Moral education is very important in forming one’s character. Moral means customs, habits, rules/procedures, values of life. Student in moral learning, especially children, need orientation, meaning, an example, witness the live score, or model that can be seen, felt, and eventually followed into action or behavior. The objectives of this research is: (1) to examine the effectiveness of learning moral through reading daily prayers and short letters of the Qur'an, (2)The implementation of the learning methods for the early children. The research method used was action research. Respondents were students of class B RA Habibillah aged 5-6 years with a number of 12 students The results of the research show that: (1). The methods of learning moral through reading daily prayers and short letters of the Qur'an is proved effective in order to form the character. The students are able to understand the daily prayers and short letters of the Qur'an and they show good behavior and manner in their daily’s school. (2) The learning process was conducted in a very specific good ways by the teachers with close relationship among the students.